Narcotics use, property crime, and dealing: Structural dynamics across the addiction career - Anglin, M. Douglas (Journal of quantitative criminology, 1986)
Structural-equation modeling is used to test causal relationships between narcotics addiction and the associated cost-support activities of property crime and drug dealing across four critical periods of the addiction career. It is argued that structural-equation methodology yields greater insight into the causal dynamics of such activities than the typical methodologies of comparing means and proportions. Using structural coefficients of longitudinal models to infer causal relationships and stability, it is found that (1) dealing is often a predictor of future narcotics involvement; (2) narcotics use, property crime, and dealing are mutually interrelated during periods of elevated narcotics use and are not related during periods of reduced narcotics use; (3) dealing appears to be the most stable of the three variables, although narcotics use and property crime show appreciable stability as well; and (4) property crime and dealing appear to be inversely related to a moderate extent. The relevance of these findings to the understanding of the economic behavior of addicts during the initiation and cessation of addiction, relapse, and “maturing out” is discussed.